Method for evaluating atmospheric corrosion resistance of weather-resistant bridge steel

By calculating the comprehensive influence of factors such as alloy composition, structure type, grain size and grain boundary characteristics of weather-resistant bridge steel, a calculation formula for the comprehensive impact corrosion resistance index W of weather-resistant bridge steel was established, which solved the problems of insufficient influencing factors, complex operation and long test cycle in the existing technology, and achieved efficient and accurate atmospheric corrosion resistance evaluation of bridge structural steel.

CN119643422APending Publication Date: 2025-03-18NORTHEASTERN UNIV CHINA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411615147.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing atmospheric corrosion resistance performance evaluation method of weather-resistant bridge steel is insufficient to consider influencing factors, complicated operation steps and long test cycles, which cannot meet the corrosion resistance performance evaluation needs of multiphase structured steel.

Method used

By calculating the comprehensive influence of factors such as alloy composition, structure type, grain size and grain boundary characteristics, a calculation formula for the comprehensive impact corrosion resistance index W of weather-resistant bridge steel is established, including the value of atmospheric corrosion resistance index I, the impact corrosion resistance index W1 of the structure type, the impact corrosion resistance index W2 of the grain size, and the low ΣCSL grain boundary fraction FCSL.

Benefits of technology

Quantitative prediction and evaluation of the atmospheric corrosion resistance of bridge structural steel is achieved, operating steps are simplified, test cycles are shortened, and evaluation accuracy and efficiency are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119643422A_ABST
    Figure CN119643422A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metal material corrosion resistance evaluation, in particular to an atmospheric corrosion resistance evaluation method for weather-proof bridge steel. According to the method, a more comprehensive, more accurate and more convenient corrosion resistance evaluation standard is established based on alloy components, structure types, grain sizes and grain boundary characteristics, a large number of laboratory accelerated simulation and outdoor exposure tests are not needed, and the limitation that a traditional corrosion resistance index I value only depends on alloy components is made up; the method has important practical significance and engineering value for service safety and durability of bridge structural steel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of corrosion resistance evaluation of metal materials, and in particular to a method for evaluating the atmospheric corrosion resistance of weather-resistant bridge steel. Background Art

[0002] Weathering bridge steel is widely used to bear the loads of various bridges due to its excellent mechanical properties and durability, and plays a vital role in bridge engineering. In recent years, with the rapid development of industry and the deteriorating environment, bridges have been exposed to atmospheric environments such as air, moisture, and salt spray for a long time, which is prone to local corrosion and structural damage, especially in coastal areas and areas with serious industrial pollution. Corrosion not only weakens the bearing capacity of steel and shortens the service life of bridges, but also requires frequent maintenance or replacement of bridge steel every year, which greatly increases the daily maintenance cost of bridges. Therefore, the atmospheric corrosion resistance of bridge structural steel has an extremely important impact on the structural safety, long service life and reduced maintenance costs of bridges. Establishing a comprehensive, complete and convenient evaluation method for the atmospheric corrosion resistance of weathering bridge steel has important practical significance and engineering value.

[0003] A large number of studies have shown that atmospheric corrosion of weather-resistant bridge steel is a very complex process, which is not only affected by external environmental conditions, but also related to the properties of the steel itself. The material's own properties mainly depend on the alloy composition, steel purity, microstructure type, grain size and grain boundary characteristics. GB / T 41756-2022 Corrosion of Metals and Alloys - Evaluation Method for Atmospheric Corrosion Resistance of Low-alloy Steels gives three evaluation methods for atmospheric corrosion resistance of low-alloy steels. Method 1 is a prediction method based on short-term corrosion data of steel; Method 2 is a prediction method based on the chemical composition of steel; Method 3 is a prediction method based on environmental factors and chemical composition of steel. Methods 1 and 3 require outdoor exposure tests, which are complicated and have long test cycles. Method 2 uses the Legault-Leckie equation to calculate the corrosion resistance index I: [I = 26.01 (% Cu) + 3.88 (% Ni) + 1.2 (% Cr) + 1.49 (% Si) + 17.28 (% P) - 7.29 (% Cu) (% Ni) - 9.1 (% Ni) (% P) - 33.39 (Cu) 2 ] is used to evaluate the atmospheric corrosion resistance of steel. This index only considers the influence of alloy composition, but ignores the influence of other factors such as microstructure type, grain size and grain boundary characteristics.

[0004] Compared with relevant patent literature, the Chinese patent application with publication number CN 111089831 A discloses "A method for evaluating the corrosion resistance of low alloy structural steel". It calculates the atmospheric corrosion resistance index I, pearlite phase content (X1), grain size grade (X2) and inclusion area percentage (X3) of the element composition of the low alloy structural steel, and establishes a formula for the comprehensive corrosion resistance index Y: Y = I-0.062X1+0.10X2-12.1X3. The corrosion resistance of the low alloy structural steel is judged by the size of the Y value. This method takes into account many influencing factors and is simple and convenient to operate. However, with the development of bridge steel, high-strength weather-resistant bridge steel mainly composed of bainite is increasingly widely used in bridge building structures. This method only considers the influence of pearlite phase in the steel structure type, which cannot meet the corrosion resistance evaluation of multi-phase structural steel (such as bainite steel, pearlite + bainite steel and ferrite + bainite steel, etc.), and does not calculate the weight ratio of the atmospheric corrosion resistance index I value in various influencing factors.

[0005] The Chinese patent application with publication number CN 118443563 A discloses "Performance evaluation method and related equipment for weathering steel", which is based on an electrochemical workstation to obtain the polarization resistance value R0 of the target weathering steel in the initial normal state and the rust layer resistance value R1 in the corroded rust state, and determines the corrosion resistance of the target weathering steel through the formula Z = (R0-R1) / R0. The larger the Z value, the better the corrosion resistance of the target weathering bridge steel. This method evaluates the protective performance of the weathering steel rust layer on the substrate through electrochemical testing technology, and the result is highly accurate, but the operation steps are complicated. First, a periodic immersion accelerated corrosion test for a certain period of time is required to obtain a rusted sample.

[0006] The Chinese patent application with publication number CN 113899681 A discloses "an evaluation method for stable rust layer of weather-resistant bridge steel in industrial atmospheric environment". It uses NaHSO3 immersion adsorption test to statistically analyze multiple groups of experimental data of solutions with different concentrations, and plots a curve with the concentration C of NaHSO3 solution as the horizontal coordinate and the ratio C / θ of the concentration C of NaHSO3 solution to the protection factor θ as the vertical coordinate. The slope R of the curve is used as the evaluation value of the corrosion resistance of the rust layer, and the R value is directly proportional to the corrosion resistance. The law of this evaluation method is consistent with the law of field exposure, and the curve fitting accuracy is good, but at least 3 NaHSO3 solutions with different concentrations need to be selected for testing, and the test time for each group is 24 to 72 hours. The operation steps are cumbersome, and the test cycle is long, which is not convenient for rapid and large-scale evaluation of the corrosion resistance of bridge structure steel.

[0007] In view of the above problems, it is very necessary to establish an evaluation method for the atmospheric corrosion resistance of weather-resistant bridge steel that takes into account multiple influencing factors, is easy to operate, has a short test cycle, and is comprehensive and accurate. This is of great significance to the service safety and long-life development of current bridge structure steel. Summary of the invention

[0008] In view of the problems existing in the existing corrosion resistance evaluation technology of weather-resistant bridge steel, such as insufficient consideration of influencing factors, complicated operating procedures and long test cycle, the present invention provides a method for evaluating the atmospheric corrosion resistance of weather-resistant bridge steel, which fully considers the influencing factors and establishes a more comprehensive, more accurate and more convenient corrosion resistance evaluation standard based on alloy composition, microstructure type, grain size and grain boundary characteristics, which has important practical significance and engineering value for the service safety and durability of bridge structure steel.

[0009] The technical solution of the present invention is:

[0010] A method for evaluating the atmospheric corrosion resistance of weather-resistant bridge steel, the method comprising the following steps:

[0011] S1: Calculate the atmospheric corrosion resistance index I value based on the chemical composition of weathering bridge steel;

[0012] S2: Obtain the phase contents of pearlite and bainite through metallographic structure, and calculate the corrosion resistance index W1 of the structure type;

[0013] S3: The average grain size of ferrite and pearlite is calculated through metallographic structure, and the average grain size of bainite is obtained by EBSD test, and the corrosion resistance index W2 of grain size is calculated;

[0014] S4: Obtain low ΣCSL (3≤Σ≤29) grain boundary fraction F through EBSD CSL grain boundary distribution map CSL ;

[0015] S5: The I value, W1, W2 and F in the above four steps are CSL Substitute into the formula lnW = 1.426I-0.051W1-0.109W2+0.290F CSL -72.268, the obtained W value is the comprehensive corrosion resistance index of weather-resistant bridge steel. The larger the W value, the better the atmospheric corrosion resistance of the steel.

[0016] Furthermore, in the above-mentioned method for evaluating atmospheric corrosion resistance of weather-resistant bridge steel, in step S1, the content of each element in the weather-resistant bridge steel is determined by photoelectric emission spectroscopy, X-ray fluorescence spectroscopy or chemical analysis method, according to the formula:

[0017] I=26.01(%Cu)+3.88(%Ni)+1.2(%Cr)+1.49(%Si)+17.28(%P)-7.29(%Cu)(%Ni)-9.1(%Ni)(%P)-33.39(Cu) 2

[0018] Calculate the atmospheric corrosion resistance index I value of the weather-resistant bridge steel to be evaluated.

[0019] Furthermore, in the above-mentioned atmospheric corrosion resistance evaluation method of a weather-resistant bridge steel, in step S2, the surface of the weather-resistant bridge steel metallographic sample is polished with 400#~2000# silicon carbide sandpaper, and then mechanically polished with 2.5mm diamond polishing paste. After being corroded with 4% nitric acid alcohol solution, the metallographic structure is observed using an optical metallographic microscope, and the ImageJ image analysis software is used to respectively count the area percentages of pearlite and bainite in the weather-resistant bridge steel to be evaluated, and the obtained values ​​are recorded as %B and %P, respectively, according to the formula:

[0020] W1=-0.253%P-0.254%B+61.469

[0021] The corrosion resistance index W1 of the influence of microstructure type was calculated.

[0022] Furthermore, in the above-mentioned method for evaluating atmospheric corrosion resistance of weather-resistant bridge steel, in step S3, the average grain sizes of ferrite and pearlite in the weather-resistant bridge steel to be evaluated are obtained by observing the metallographic structure image and according to "GB / T 6394-2017 Method for Determination of Average Grain Size of Metals", and the obtained values ​​are recorded as d F and d P , unit μm, the surface of the weather-resistant bridge steel sample was polished with 400#~2000# silicon carbide sandpaper, then electrolytically polished, and EBSD test was performed. The average grain size d of bainite in the weather-resistant bridge steel to be evaluated was obtained using HKL-Channel5 software B , unit μm, according to the formula:

[0023] W2=0.279d F +0.286d P +0.987d B +39.143

[0024] The corrosion resistance index W2 of grain size was calculated.

[0025] Furthermore, in the above-mentioned atmospheric corrosion resistance evaluation method of a weather-resistant bridge steel, in step S4, the EBSD test data is processed by HKL-Channel 5 software to obtain the CSL grain boundary distribution map, and the Brandon criterion Δθ=15°Σ -1 / 2Classify the CSL grain boundary characteristics and obtain the low ΣCSL (3≤Σ≤29) grain boundary fraction F of the weathering bridge steel to be evaluated CSL .

[0026] Furthermore, in the above-mentioned method for evaluating the atmospheric corrosion resistance of weather-resistant bridge steel, when obtaining the phase content of pearlite and bainite in step S2 and obtaining the average grain size of ferrite, pearlite and bainite in step S3, at least three fields of view need to be randomly selected for statistics.

[0027] Advantages and beneficial effects of the present invention:

[0028] 1. The present invention comprehensively considers the influence of factors such as alloy composition, organizational type, grain size and grain boundary characteristics of weather-resistant bridge steel on the atmospheric corrosion resistance of steel, calculates the influence weight of each influencing factor on corrosion resistance, and gives a quantitative relationship, which makes up for the deficiency that the traditional atmospheric corrosion resistance I value only depends on the alloy composition, and has important practical significance and engineering value for the service safety and long-life development of bridge structure steel.

[0029] 2. The present invention only needs to detect and count parameters such as the alloy composition, organizational type, grain size and grain boundary characteristics of weather-resistant bridge steel, avoiding traditional outdoor field exposure tests, laboratory corrosion simulation accelerated tests or electrochemical tests. The operation steps are simple, which greatly reduces the test cycle and can accurately and efficiently complete the atmospheric corrosion resistance evaluation of bridge structure steel. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The metallographic structure of the weather-resistant bridge steel of Example 1-8;

[0031] Figure 2 is the inverse pole figure of the weather-resistant bridge steel of Examples 1-8;

[0032] Figure 3 This is the CSL grain boundary distribution diagram of the weather-resistant bridge steel of Examples 1-8. DETAILED DESCRIPTION

[0033] In order to better understand the scheme and advantages of the present invention, the specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples of the specification. It should be understood that the following examples are only used for illustration and explanation of the present invention, but cannot be used to limit the scope of the present invention.

[0034] Examples 1-8

[0035] The alloy composition of eight types of bridge steels used in the embodiment of the method for evaluating the atmospheric corrosion resistance of weather-resistant bridge steel described in the present invention is shown in Table 1.

[0036] Table 1 Alloy composition of weather-resistant bridge steel used in Examples 1-8 (mass, %)

[0037]

[0038]

[0039] According to the calculation formula

[0040] I=26.01(%Cu)+3.88(%Ni)+1.2(%Cr)+1.49(%Si)+17.28(%P)-7.29(%Cu)(%Ni)-9.1(%Ni)(%P)-33.39(Cu) 2 The atmospheric corrosion resistance index I values ​​of the weather-resistant bridge steels of Examples 1-8 are obtained, as shown in Table 2.

[0041] Table 2 Atmospheric corrosion resistance index I value of weathering bridge steel of Examples 1-8

[0042] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 I 7.09 7.01 6.90 7.70 7.18 6.99 6.90 6.71

[0043] The weather-resistant bridge steel of Example 1-8 was cut into metallographic specimens of 10 mm × 8 mm × 5 mm (rolling direction × width direction × thickness direction) by using electric spark wire cutting, and after being polished by 400#~2000# silicon carbide sandpaper, mechanically polished by using 2.5 mm diamond polishing paste, and after being corroded by 4% nitric acid alcohol solution, its metallographic structure was observed by using an optical metallographic microscope. Figure 1 As shown, the area percentage %P of pearlite and the area percentage %B of bainite in the steels of Examples 1-8 were statistically analyzed using Image J image analysis software, and the results are shown in Table 3.

[0044] Table 3 Area percentage of pearlite and bainite in weathering bridge steel of Examples 1-8

[0045] P / % B / % Example 1 5 53 Example 2 16 21 Example 3 9 29 Example 4 0 57 Example 5 0 62 Example 6 12 29 Example 7 6 34 Example 8 4 17

[0046] Substitute the area percentage %P of pearlite and the area percentage %B of bainite in the steels of Examples 1-8 in Table 3 into the formula W1=-0.253%P-0.254%B+61.469 to calculate the corrosion resistance index W1 affected by the microstructure type.

[0047] The average grain sizes of ferrite and pearlite in the eight example steels were statistically analyzed by metallographic images according to GB / T 6394-2017 Method for Determination of Average Grain Size of Metals, and the obtained values ​​were recorded as d F and d P, unit μm. The eight embodiments were cut into 8mm×6mm×3mm (rolling direction×width direction×thickness direction) samples by wire electrospark cutting, polished with 400#~2000# silicon carbide sandpaper, and electrolytic polished in a ratio solution of 10% HClO4 and 90% CH3COOH. EBSD detection was performed using a field emission scanning electron microscope, and the inverse pole figure was obtained after processing with HKL-Channel 5 software as shown in FIG. Figure 2 As shown, the average grain size d of bainite in the steels of Examples 1-8 is statistically B , unit: μm, the results are shown in Table 4.

[0048] Table 4 Average grain sizes of ferrite, pearlite and bainite in weathering bridge steels of Examples 1-8

[0049] <![CDATA[d F / μm]]> <![CDATA[d P / μm]]> <![CDATA[d B / μm]]> Example 1 9.3 3.7 5.6 Example 2 5.4 4.9 7.5 Example 3 8.2 7.3 8.2 Example 4 4.4 0 4.3 Example 5 6.4 0 5.2 Example 6 9.0 6.8 7.6 Example 7 10.7 11.4 9.3 Example 8 9.7 10.3 11.5

[0050] Substitute the average grain sizes of ferrite, pearlite and bainite in Table 4 into the formula W2 = 0.279d F +0.286d P +0.987d B +39.143, and the grain size effect corrosion resistance index W2 was obtained.

[0051] The W1 and W2 values ​​of the steels of Examples 1-8 are shown in Table 5.

[0052] Table 5 Effect of microstructure type on corrosion resistance index W1 and grain size on corrosion resistance index W2 of weathering bridge steel of Examples 1-8

[0053]

[0054]

[0055] HKL-Channel 5 software was used to process the EBSD data to obtain the CSL grain boundary distribution diagram of the steels in Examples 1-8. Figure 3 As shown, the low ΣCSL (3≤Σ≤29) grain boundary fraction is counted and recorded as F CSL , the results are shown in Table 6.

[0056] Table 6 Low ΣCSL (3≤Σ≤29) grain boundary fraction F of weathering bridge steel of Examples 1-8 CSL

[0057] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 <![CDATA[F CSL / %]]> 73 71 62 86 78 68 60 53

[0058] The weather-resistant bridge steels of Examples 1-8 were cut into corrosion specimens of 60 mm × 40 mm × 4 mm along the rolling direction. The surfaces of the specimens were polished with 400# to 1500# silicon carbide sandpaper, and then ultrasonically cleaned with petroleum ether-alcohol-acetone. After drying for 24 hours, the original weight (accurate to 0.001 g) and size (accurate to 0.01 mm) of each specimen were measured. All the samples of the examples were hung in a dry-wet alternating cycle immersion corrosion test device to carry out a simulated industrial atmospheric corrosion test. The test parameters were based on the test data of TB / T2375-1993 Cyclic Infiltration and Corrosion Test of Weathering Steel for Railways. The corrosion test method was carried out, with a cycle time of 60 minutes, including 12 minutes of immersion time and 48 minutes of drying time. During the test, the temperature of the corrosion solution was (45±2)°C, the relative humidity was (70±5)%, the baking temperature of the test surface did not exceed 70°C, the corrosion solution was 0.01 mol / L NaHSO3 solution, the pH value was 4.4-4.8, the replenishing solution was 0.02 mol / L NaHSO3 solution, the corrosion time was 72h, and three parallel samples were prepared for each example steel for corrosion rate calculation. The comparison steel was plain carbon steel Q345B.

[0059] After the corrosion test, the sample was ultrasonically cleaned in a rust removal solution (500 mL hydrochloric acid + 500 mL deionized water + 5 g hexamethylenetetramine) to remove surface corrosion products, then cleaned with anhydrous ethanol and acetone, dried with cold air for 24 hours and weighed. The corrosion rate calculation formula for the example steel and the comparative steel is as follows:

[0060]

[0061] In the formula, C R is the annual average corrosion rate of steel (mm / a), w0 and w1 are the initial mass of the sample and the mass after removing corrosion products (g), ρ is the density of steel (g / cm 3 ), t is the corrosion time (h).

[0062] The relative corrosion rate of the test steel is calculated according to the formula R corr =C R试验钢 / C R对比钢 ×100%, respectively calculate the relative corrosion rate R of the weather-resistant bridge steel of Examples 1-8 corr , the results are shown in Table 7.

[0063] Table 7 Relative corrosion rate values ​​R of weather-resistant bridge steel of Examples 1-8 corr

[0064] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 <![CDATA[R corr / %]]> 48.2 49.7 53.5 43.5 46.4 51.4 53.8

[0065] The relative corrosion rate value R of the weather-resistant bridge steel in Example 1-8 is corrThe natural logarithm of the atmospheric corrosion resistance index I, the corrosion resistance index W1 affected by the microstructure type, the corrosion resistance index W2 affected by the grain size, and the low ΣCSL (3≤Σ≤29) grain boundary fraction F were used as the dependent variable. CSL As the independent variable, multivariate regression fitting was performed. According to the negative correlation between relative corrosion rate and corrosion resistance, the coefficients of each independent variable were corrected and the constant terms were combined. The relationship between the comprehensive corrosion resistance index W of weather-resistant bridge steel and the above four influencing factors was obtained as follows:

[0066] lnW=1.426I-0.051W1-0.109W2+0.290F CSL -72.268

[0067] From the above expression, it can be seen that the larger the W value is, the better the atmospheric corrosion resistance of the weathering steel is. Therefore, the atmospheric corrosion resistance evaluation method of weathering bridge steel in the present invention can be used to quantitatively predict and evaluate the corrosion resistance of bridge structure steel.

[0068] The above are only some embodiments, which are only for better explanation of the present invention, not for limitation. A person skilled in the art may modify some technical features of the above embodiments, but any modification made within the principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for evaluating the atmospheric corrosion resistance of weather-resistant bridge steel, characterized in that: The evaluation method comprises the following steps: S1: Calculate the atmospheric corrosion resistance index I value based on the chemical composition of weathering bridge steel; S2: Obtain the phase contents of pearlite and bainite through metallographic structure, and calculate the corrosion resistance index W1 of the structure type; S3: The average grain size of ferrite and pearlite is calculated through metallographic structure, and the average grain size of bainite is obtained by EBSD test, and the corrosion resistance index W2 of grain size is calculated; S4: Obtain low ΣCSL (3≤Σ≤29) grain boundary fraction F through EBSD CSL grain boundary distribution map CSL ; S5: The I value, W1, W2 and F in the above four steps are CSL Substitute into the formula lnW = 1.426I-0.051W1-0.109W2+0.290F CSL -72.268, the obtained W value is the comprehensive corrosion resistance index of weather-resistant bridge steel. The larger the W value, the better the atmospheric corrosion resistance of the steel.

2. The method for evaluating atmospheric corrosion resistance of weather-resistant bridge steel according to claim 1, characterized in that: In step S1, the content of each element in the weather-resistant bridge steel is determined by photoelectric emission spectroscopy, X-ray fluorescence spectroscopy or chemical analysis method, according to the formula: I=26.01(%Cu)+3.88(%Ni)+1.2(%Cr)+1.49(%Si)+17.28(%P)-7.29(%Cu)(%Ni)-9.1(%Ni)(%P)-33.39(Cu) 2 Calculate the atmospheric corrosion resistance index I value of the weather-resistant bridge steel to be evaluated.

3. The method for evaluating atmospheric corrosion resistance of weather-resistant bridge steel according to claim 1, characterized in that: In step S2, the surface of the weather-resistant bridge steel metallographic sample is polished with 400# to 2000# silicon carbide sandpaper, and then mechanically polished with 2.5mm diamond polishing paste. After being etched with 4% nitric acid alcohol solution, the metallographic structure is observed using an optical metallographic microscope. The Image J image analysis software is used to count the area percentages of pearlite and bainite in the weather-resistant bridge steel to be evaluated, and the obtained values ​​are recorded as %B and %P, respectively, according to the formula: W1=-0.253%P-0.254%B+61.469 The corrosion resistance index W1 of the influence of microstructure type was calculated.

4. The method for evaluating atmospheric corrosion resistance of weather-resistant bridge steel according to claim 1, characterized in that: By observing the metallographic structure image and according to GB / T 6394-2017 Method for Determination of Average Grain Size of Metals, the average grain sizes of ferrite and pearlite in the weathering bridge steel to be evaluated are obtained, and the obtained values ​​are recorded as d F and d P , unit μm, the surface of the weather-resistant bridge steel sample was polished with 400#~2000# silicon carbide sandpaper, then electrolytically polished, and EBSD test was performed. The average grain size d of bainite in the weather-resistant bridge steel to be evaluated was obtained using HKL-Channel 5 software B , unit μm, according to the formula: <h2 style=";text-align:left;direction:ltr">W2 = 0.279d<h2 style=";text-align:left;direction:ltr"> F <h2 style=";text-align:left;direction:ltr"> +0.286d<h2 style=";text-align:left;direction:ltr"> P <h2 style=";text-align:left;direction:ltr"> +0.987d<h2 style=";text-align:left;direction:ltr"> B <h2 style=";text-align:left;direction:ltr"> +39.143 The corrosion resistance index W2 of grain size was calculated.

5. The method for evaluating atmospheric corrosion resistance of weather-resistant bridge steel according to claim 1, characterized in that: The CSL grain boundary distribution map was obtained by processing the EBSD test data with HKL-Channel 5 software, and the Brandon criterion Δθ=15°Σ -1 / 2 Classify the CSL grain boundary characteristics and obtain the low ΣCSL (3≤Σ≤29) grain boundary fraction F of the weathering bridge steel to be evaluated CSL .

6. The method for evaluating atmospheric corrosion resistance of weather-resistant bridge steel according to claim 1, characterized in that: When obtaining the phase contents of pearlite and bainite in step S2 and the average grain sizes of ferrite, pearlite and bainite in step S3, at least three viewing fields need to be randomly selected for statistics.

Citation Information

Patent Citations

  • Corrosion resistance evaluation method for low alloy structural steel

    CN111089831A

  • Evaluation method of weather-proof bridge steel stable rust layer in industrial atmospheric environment

    CN113899681A

  • Weathering steel performance evaluation method and related equipment

    CN118443563A